Validity and feasibility of a predictive language screening tool in 2-year-old children in primary pediatric care - Holzinger, Daniel; Weber, Christoph; Fellinger, Johannes (Frontiers in Pediatrics, 2022)
Objective: To assess the predictive validity and feasibility of the newly developed language screening tool, SPES-2 (Sprachentwicklungsscreening), for 2-year-old children in pediatric primary care. Methods: A prospective cohort study recruited 2,044 non-selected German-speaking children undergoing a regular well-baby check-up at the age of 2 years. Thirty primary care pediatricians spread over urban and rural areas screened the children using a short parent-reported questionnaire and direct assessment of word comprehension. To validate the screening tool, language skills were assessed using a standardized language screening tool in the complete sample one year later. Data of a random sample of 621 children were analyzed. Feasibility of the screening tool was evaluated using questionnaires completed by the participating pediatricians. Results: The new screening tool, SPES-2, demonstrated good diagnostic accuracy with AUC (Area under the Roc Curve) of 0.885, a sensitivity of 0.74, and specificity of 0.86, using a parent-reported questionnaire (expressive vocabulary, two-word combinations, parental concerns) as stage 1, followed by a stage 2 direct assessment of word comprehension by the pediatrician. The second stage was restricted to children who failed the parental screening. The screening identified children with high, moderate, and low risk of significant language deficits (SLD) at the age of 3 years, permitting tailored follow-up assessment and parental counseling. Practicability and acceptability of the screening were mostly rated as high. Pediatricians regarded the availability of follow-up diagnostic services and parent guidance as most important for a general implementation of the new instrument. Conclusion: The language screening tool, SPES-2, was valid for the identification of significant language deficits one year later, and considered as feasible within primary pediatric care.